2021
DOI: 10.1177/09603271211027948
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting p21-activated kinase (PAK7) enhances radiosensitivity in hepatocellular carcinoma

Abstract: Objective: In light of the upregulation of p21-activated kinase (PAK7) in a variety of cancers, including hepatocellular carcinoma (HCC), we aimed to investigate the effect of PAK7 on the sensitivity of HCC cells to radiotherapy. Methods: PAK7 expression was determined in normal adult liver epithelial THLE-2 and human HCC cell lines. The effect of ionizing radiation (IR) on the HCC cell viability was evaluated by Sulforhodamine B (SRB) assay. HCC cell lines Mahlavu and Huh7 were chosen to assess the effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…6 ). Previous studies have reported that PAK7 exerts an antiapoptotic function in multiple tumor cell lines [ 43 45 ]. Similarly, our findings show that PAK7 knockdown enhances LPS-induced apoptosis in BUMPT cells through the Wnt/β-catenin pathway (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…6 ). Previous studies have reported that PAK7 exerts an antiapoptotic function in multiple tumor cell lines [ 43 45 ]. Similarly, our findings show that PAK7 knockdown enhances LPS-induced apoptosis in BUMPT cells through the Wnt/β-catenin pathway (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…PAK5 and ABCB1 are positively correlated in HCC patient samples [103]. In HCC, cells expressing high PAK7 are resistant to radiation and enhance radiosensitivity through increasing H2AX [104] In lung cancer cells, PAK5 interacts with Sox2 and phosphorylates Sox2. It also regulates the other stem cell markers such as ALDH, Nanog, Oct3/4, and Sox2 [105].…”
Section: Pak5/7 In Drug Resistancementioning
confidence: 99%
“…Radiation-induced senescence is mainly controlled by the activation of the p53-p21 pathway and the p16 INK4a -retinoblastoma protein (pRB) pathway [14,100]. After ionizing radiation damages tumor cell DNA, activated p53 upregulates the expression of p21, a cyclin-dependent kinase (CDK) inhibitor that inhibits the expression of CDK-cyclin complexes [101][102][103]. Inhibition of CDK1-cyclin A complex arrests cells in the G2/M phase [101,103].…”
Section: Radiotherapy and Senescencementioning
confidence: 99%